2019
DOI: 10.1002/joe.21976
|View full text |Cite
|
Sign up to set email alerts
|

How work values and organizational outcomes differ by generational cohort in Malaysia's manufacturing sector

Abstract: An empirical study of 164 employees at seven large‐scale manufacturers in Malaysia's Penang Free Trade Zone suggests that work values, job satisfaction, organizational commitment, and turnover intention of various generational cohorts differ. Baby Boomers have a higher level of organizational commitment and job satisfaction than their coworkers in Generation X and Generation Y, while Generation Xers have the lowest level of intention to quit. In addition, Baby Boomers have a high level of intrinsic, altruistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…This is what a blockchain-driven system can address and absorb much of the data integrity problems and demonstrate transparency across the value chain. These challenges are often enhanced as employees have different work values, which impact organizational outcomes, especially for manufacturing industries in emerging and developing markets (Hung Kee et al , 2019). The theoretical lens is illustrated in Figure 4.…”
Section: Methodsmentioning
confidence: 99%
“…This is what a blockchain-driven system can address and absorb much of the data integrity problems and demonstrate transparency across the value chain. These challenges are often enhanced as employees have different work values, which impact organizational outcomes, especially for manufacturing industries in emerging and developing markets (Hung Kee et al , 2019). The theoretical lens is illustrated in Figure 4.…”
Section: Methodsmentioning
confidence: 99%
“…Psychological satisfaction with work is reflected as an intrinsic value, which is further classified into autonomy, aesthetics, creativity, lifestyle, achievement, variety, challenge and altruism and these are positively related to intrinsic rewards (Hartung et al , 2010; Hung Kee et al , 2019). However, few work values are considered as equivocal to be taken as intrinsic and extrinsic rewards with significant extents.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Values can provide knowledge about how people evaluate the importance of various events and how they get motivated in varied circumstances to commence different activities. In a similar way, work values help employees in determining the importance of their assigned work and how they can accomplish their targets (Hung Kee et al , 2019). Until recently, the research fraternity has mostly focussed on general values instead of work values (Arieli et al , 2020; Basinska and Dåderman, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Taking the case of a Malaysian context, Hung Kee, Ching, and Ng (2019) found different work values, job satisfaction, organisational commitment, and intention to quit working across different generations based on a sample of 164 employees at seven major manufacturers in the Penang Free Industrial Zone. The study further revealed that baby boomers had a higher level of organisational commitment and job satisfaction and the lowest intention to quit working than their colleagues of Generation X and Generation Y.…”
Section: The Relationship Between Multi-generation and Intention To Quit Workingmentioning
confidence: 99%
“…Understanding generation differences among the employees can help to minimise conflicts between the organisation and its employees. Conflicts can affect communication among the employees and negatively affect organisational productivity and performance (Hung Kee et al, 2019). Therefore, there is a strong need to study the behavioural differences by generation cohort in order to discover the real potential and suitability of the employees in an organisation (Cennamo & Gardner, 2008;Taylor, 2017;Hung Kee, Ching, & Ng, 2019).…”
Section: Introductionmentioning
confidence: 99%